2015
DOI: 10.5455/medarh.2015.69.334-338
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Pressure Measurements Referring to the Corneal Thickness in Keratoconic Eyes After Corneal Crosslinking with Riboflavin and Ultraviolet A

Abstract: Aim:To determine the possible relation between intraocular pressure (IOP), central corneal thickness (CCT) and corneal resistance (CR) in kerotoconic eyes before, 3,6 and 12 months after collagen crosslinking procedure (CXL) with aim to find out does the thicker cornea means already more resistance cornea followed with higher IOP.Methods:Thirty eyes (30 patients) with central keratoconus (KC)were evaluated in retrospective cross sectional study. The corneal biomechanical parameters were taken with Wave Light A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 22 publications
2
12
0
1
Order By: Relevance
“…The low IOP measurements in eyes with keratoconus are attributed to low corneal rigidity and corneal thinning. 30 In our study, we observed increases in both mean IOPg and IOPcc in the early and late postoperative periods after CXL. However, only the increase in IOPg seen in the early postoperative period was statistically significant.…”
Section: Discussionsupporting
confidence: 54%
“…The low IOP measurements in eyes with keratoconus are attributed to low corneal rigidity and corneal thinning. 30 In our study, we observed increases in both mean IOPg and IOPcc in the early and late postoperative periods after CXL. However, only the increase in IOPg seen in the early postoperative period was statistically significant.…”
Section: Discussionsupporting
confidence: 54%
“…In comparison, a thinner cornea with scaring may have an artefactually higher reading due to increased rigidity. The increased rigidity in the cornea after cornea crosslinking has been postulated to explain the increase in IOP observed in keratoconus patients after 1 year, despite no change in their CCT [33].…”
Section: Artifact and Correctionmentioning
confidence: 99%
“…This indicates that elevated measured IOP after CXL showed a stiffer behavior of the eye wall, especially the cornea. An increased IOP in Goldmann applanation tonometry after CXL was reported in vivo by Kymionis et al and Kasumovic et al [ 44 , 45 ]. The deflection amplitude was significantly decreased in all protocols, even though CT was adjusted.…”
Section: Discussionmentioning
confidence: 78%